Mixed effectiveness of rTMS and retraining in the treatment of focal hand dystonia - Kimberley, Teresa J.; Schmidt, Rebekah; Chen, Mo; Dykstra, Dennis D.; Buetefisch, Cathrin M. (Frontiers in Human Neuroscience, 2015)
Though the pathophysiology of dystonia remains uncertain, two primary factors implicated in the development of dystonic symptoms are excessive cortical excitability and impaired sensorimotor processing. The aim of this study was to determine the functional efficacy of a sensorimotor intervention combining rTMS and sensorimotor retraining. A randomized, single-subject, multiple baseline design with crossover was used to examine participants with focal hand dystonia (FHD) (n=9). Intervention: 5 days rTMS + sensorimotor retraining (SMR) vs. 5 days rTMS + control therapy (CTL) (which included stretching and massage). The rTMS was applied to the premotor cortex at 1 Hz at 80% resting motor threshold for 1200 pulses. For sensorimotor retraining, a subset of the Learning-based Sensorimotor Training program was followed. Each session consisted of rTMS followed immediately by 30 minutes of the therapy intervention (SMR or CTL). Group analyses revealed no additional benefit from the SMR training vs CTL, which was contrary to our hypothesis. When analyzed across group however, there was significant improvement from first baseline in several measures, including tests of sensory ability and self-rated changes. The patient rated improvements were accompanied by a moderate effect size suggesting clinical meaningfulness. These results provide encouragement for further investigation of rTMS in FHD with a need to optimized a secondary intervention and determine likely responders vs. non-responders.